Nutrition in pregnancy and lactation: how a healthy infant is born - Federico Mecacci; Sara Biagioni; Serena Ottanelli; Giorgio Mello (Hygeia Press di Corridori Marinella, 2015)
Maternal nutrition during pregnancy and lactation influences the growth and potential development of the fetus and contributes to the maturity of a healthy baby. The lack of sufficient calories, of macro- and micronutrients, can lead to deficiencies in building materials for the development and growth of the fetus: moreover there is growing evidence that the maternal nutritional status can alter the epigenetic state of the fetal genome, therefore alterations in nutrition during crucial periods of fetal development may result in developmental adaptations that permanently change the physiology, the metabolism of the offspring, and, as a consequence, predispose these individuals to diseases as adults. In this review we collected indications for the recommended intake of calories and nutrients for a healthy diet during pregnancy and lactation, also analyzing some nutritional choices that may increase the risk of nutritional deficiencies and the way to prevent them. Pregnancy-related dietary changes should begin prior to conception, with appropriate modifications throughout pregnancy and lactation, and appropriate supplementation of vitamins and minerals.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)